Epidemiologi HIV di Kota Medan Tahun 2021-2023 - Tanjung, Hazira Yulistia; Ismah, Zata; Susanti, Nofi (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT  The importance of descriptive epidemiology based on people, place and time in HIV sufferers is known, in order to improve case finding and provide prevention and control programs to groups at risk. The city of Medan is the largest contributor to HIV cases in North Sumatra. RSU Haji Medan, is an HIV Referral Hospital, and a free ARV provider that can be an HIV representative in Medan City. To provide descriptive epidemiology and a map of the distribution of HIV sufferers in Medan City in 2021-2023. Quantitative type is descriptive using a cross-sectional design using medical record data. The sampling used was Exhaustive Sampling with a total of 121 samples. All data were analyzed using univariate analysis techniques, data on the sub-district where the patient lived was processed using QGIS 3.34.3 to see the distribution of residences of positive patients. The results showed that PLHIV had the most age characteristics, namely age 25-49 years (68.6%), male gender (75.2%), high school education (39.7%), not working (39.7%), and married (55.6%). Most people suffering from IO TB were men (60.0%), working (53.3%), and aged 25-49 years (73.3%), as well as hypertension. Most HIV cases are adults, male, have a high school education, are married, and work. Likewise, PLHIV who suffer from TB and hypertension are mostly adults, male and working. Medan Tembung District has the highest HIV cases in Medan City. Keywords: Descriptive Epidemiology, HIV, Medan City  ABSTRAK Pentingnya Epidemiologi Deskriptif berdasarkan orang, tempat, dan waktu pada penderita HIV diketahui, agar dapat meningkatkan penemuan kasus dan pemberian program pencegahan dan pengendalian kepada kelompok yang berisiko. Kota Medan penyumbang terbesar kasus HIV di Sumatera Utara. RSU Haji Medan, merupakan RS Rujukan HIV, dan penyedia ARV gratis yang dapat menjadi representatif HIV di Kota Medan. Untuk menggambarkan secara epidemiologi deskriptif dan peta sebaran penderita HIV di Kota Medan tahun 2021-2023. Jenis Kuantitatif bersifat deskriptif menggunakan desain cross sectional melalui data rekam medik. Pengambilan sampel yang digunakan yaitu Exhaustive Sampling dengan total 121 sampel. Seluruh data dianalisis dengan teknik analisis univariat, data kecamatan tempat tinggal ODHIV diolah menggunakan QGIS 3.34.3 untuk melihat sebaran tempat tinggal ODHIV. Didapatkan hasil ODHIV memiliki karakteristik usia terbanyak yaitu umur 25-49 tahun (68,6%), jenis kelamin laki-laki (75,2%), pendidikan SMA (39,7%), tidak bekerja (39,7%), dan sudah menikah (55,6%). Menderita IO TB paling banyak adalah laki-laki (60,0%), bekerja (53,3%), dan umur 25-49 tahun (73,3%), begitupun dengan Hipertensi.  Kasus HIV paling banyak adalah orang dewasa, berjenis kelamin laki-laki, berpendidikan SMA, sudah menikah, serta bekerja. Begitupun ODHIV yang menderita TB dan Hipertensi paling banyak orang dewasa, berjenis kelamin laki-laki, dan bekerja. Kecamatan Medan Tembung memiliki kasus HIV tertinggi di Kota Medan. Kata Kunci: Epidemiologi Deskriptif, HIV, Kota Medan